Identification of species and materia medica within Saussurea subg. Amphilaena based on DNA barcodes - Chen, Jie; Zhao, Yong-Bao; Wang, Yu-Jin; Li, Xiao-Gang (PeerJ, 2019)
Saussurea is one of the most species-rich genera in the family Asteraceae, where some have a complex evolutionary history, including radiation and convergent evolution, and the identification of these species is notoriously difficult. This genus contains many plants with medical uses, and thus an objective identification method is urgently needed. Saussurea subg. Amphilaena is one of the four subgenera of Saussurea and it is particularly rich in medical resources, where 15/39 species are used in medicine. To test the application of DNA barcodes in this subgenus, five candidates were sequenced and analyzed using 131 individuals representing 15 medical plants and four additional species from this subgenus. Our results suggested that internal transcribed spacer (ITS) + rbcL or ITS + rbcL + psbA-trnH could distinguish all of the species, while the ITS alone could identify all of the 15 medical plants. However, the species identification rates based on plastid barcodes were low, i.e., 0% to 36% when analyzed individually, and 63% when all four loci were combined. Thus, we recommend using ITS + rbcL as the DNA barcode for S. subg. Amphilaena or the ITS alone for medical plants. Possible taxonomic problems and substitutes for medicinal plant materials are also discussed.
Keywords: Saussurea subg. Amphilaenais; Medical plant; Taxonomic problem; DNA barcoding; Substitute